2013
DOI: 10.3390/agronomy3040685
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterisation of New Microbial Antagonists for Biocontrol of Monilinia laxa, the Causal Agent of Brown Rot on Stone Fruit

Abstract: Abstract:Monilinia laxa is the causal agent of brown rot disease on stone fruits, and also causes blossom wilt and twig canker. The common practice used to manage this disease is through fungicide treatments. However the demand to reduce fungicide inputs has been increasing and there is a growing number of reports of M. laxa strains that are resistant to fungicides. There is an urgent need to search for an alternative strategy to control the disease. This study focused on the isolation and characterisation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…strains (Pusey and Wilson, 1984;Altindag et al, 2006;Yañez-Mendizabal et al, 2010;Liu et al, 2011;Rungjindamai et al, 2013;Gao et al, 2016). The high efficacy against brown rot of BUZ-14 endospores is very interesting as they are more stable than vegetative cells maintaining their viability for years and far more resistant to drying processes for powder formulations (Brannen and Kenney, 1997) Figure 3.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…strains (Pusey and Wilson, 1984;Altindag et al, 2006;Yañez-Mendizabal et al, 2010;Liu et al, 2011;Rungjindamai et al, 2013;Gao et al, 2016). The high efficacy against brown rot of BUZ-14 endospores is very interesting as they are more stable than vegetative cells maintaining their viability for years and far more resistant to drying processes for powder formulations (Brannen and Kenney, 1997) Figure 3.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One of the first formulated postharvest biocontrol products, now widely used, BioSave TM (JetHarvest Solutions) is based on a saprophytic strain of Pseudomonas syringae active against number of postharvest decaying fungi, but not Monilinia . Many studies since than reported antagonists effective against M. laxa , including Aureobasidium pullulans (Mari et al, 2012; Rungjindamai et al, 2013; Di Francesco et al, 2017); Pantoea agglomerans (Bonaterra et al, 2003); and Bacillus amyloliquefaciens (Rungjindamai et al, 2013) as well as some Pseudomonas spp. (Altindag et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indar inhibits sterol biosynthesis of M. laxa and directly targets the pathogen under most environmental circumstances. In contrast, biocontrol mechanisms of Y126 and B91 involve competition for nutrients and production of inhibitory compounds (Rungjindamai et al 2013), which are more likely to be influenced by external conditions. One of the challenges in biocontrol of plant pathogens is to fully understand the ecology of each BCA in order to optimise its application strategy under field conditions (Xu and Jeger 2013a, b).…”
mentioning
confidence: 96%
“…This may be because Y126 can survive low temperatures better than B91 (Rungjindamai et al 2013) [note that a different isolate of the same Bacillus species is the active ingredient of Serenade]. Application of a formulated product of another A. pullulans strain during cherry blossom led to a significant reduction in the disease incidence (Holb and Kunz 2013).…”
mentioning
confidence: 97%
See 1 more Smart Citation